2016
DOI: 10.1177/003335491613100210
|View full text |Cite
|
Sign up to set email alerts
|

Online Hookup Sites for Meeting Sexual Partners among Men Who Have Sex with Men in Rhode Island, 2013: A Call for Public Health Action

Abstract: Frequent use of websites and mobile telephone applications (apps) by men who have sex with men (MSM) to meet sexual partners, commonly referred to as "hookup" sites, make them ideal platforms for HIV prevention messaging. This Rhode Island case study demonstrated widespread use of hookup sites among MSM recently diagnosed with HIV. We present the advertising prices and corporate social responsibility (CSR) programs of the top five sites used by newly diagnosed HIV-positive MSM to meet sexual partners: Grindr, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 14 publications
2
44
0
Order By: Relevance
“…That meeting sex partners online was retained in a multivariate model that tested ten possible antecedents intimates the possible utility of this behavior as a general marker for risk and thereby supports the concept of developing corresponding online approaches to the clinic-based promotion of safer sex for YBMSM. Emerging evidence suggests that making such online programs available through the same hook-up sites that men use may be efficacious (Chan et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…That meeting sex partners online was retained in a multivariate model that tested ten possible antecedents intimates the possible utility of this behavior as a general marker for risk and thereby supports the concept of developing corresponding online approaches to the clinic-based promotion of safer sex for YBMSM. Emerging evidence suggests that making such online programs available through the same hook-up sites that men use may be efficacious (Chan et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that these digital venues may facilitate multiple partnerships and other HIV risk behaviors for MSM who already engage in these behaviors rather than act as a catalyst for these behaviors themselves [ 12 ]. However, while social and sexual network apps are accepted by MSM for HIV prevention and sexual health messaging [ 13 ], some companies who produce these geosocial-networking apps are ambiguous in their willingness to support HIV prevention programs [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reliance on traditional notification methods in the context of frequently reported anonymous partners and partners met online underlies a barrier faced universally by PNS in all six New England states. A 2013 Rhode Island study found that 60% of MSM newly diagnosed with HIV had used a hook-up app or website to meet sexual partners in the year prior to their diagnosis [ 14 ]. IPN has demonstrated the potential for health organizations to utilize hookup apps and websites in an effort to better engage, and reduce transmission of HIV and other STDs in this population [ 9 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%